2008
DOI: 10.1186/1471-2164-9-77
|View full text |Cite
|
Sign up to set email alerts
|

Mobile phone radiation might alter protein expression in human skin

Abstract: Background: Earlier we have shown that the mobile phone radiation (radiofrequency modulated electromagnetic fields; RF-EMF) alters protein expression in human endothelial cell line. This does not mean that similar response will take place in human body exposed to this radiation. Therefore, in this pilot human volunteer study, using proteomics approach, we have examined whether a local exposure of human skin to RF-EMF will cause changes in protein expression in living people.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
43
0

Year Published

2009
2009
2018
2018

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 82 publications
(43 citation statements)
references
References 13 publications
0
43
0
Order By: Relevance
“…Recently, proteomic analysis from radiation exposure subjects has been addressed 12 . Tapio et al, 2013, described a series of changes for different blood proteins, as SILAC, which is very sensitive to radiation, due to inhibition of its synthesis 13 .By contrast, Nylund et al, 2013, reported no changes in the protein expressions of the endothelial cell line (EA.hy926) submitted to radiation 13,14 .Yan et al, 2010, described the metabolism increase of skin fibroblasts and concluded that such behavior is due to resistance mechanisms of radiation cells 15 .Further studies, Yuasa et al, 2006, showed that the changes in protein expressions shall start with the interactions of radiation in the process of DNA replication, which can be occasional or permanent, and this gene reprogramming transmitted to new populations or new cell generations 16 . In additional studies, involving electromagnetic radiation such as cell phone signal or computer, Karinem et al, 2008, based on a female volunteer group, showed small changes in skin protein expressions although not conclusive 17 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, proteomic analysis from radiation exposure subjects has been addressed 12 . Tapio et al, 2013, described a series of changes for different blood proteins, as SILAC, which is very sensitive to radiation, due to inhibition of its synthesis 13 .By contrast, Nylund et al, 2013, reported no changes in the protein expressions of the endothelial cell line (EA.hy926) submitted to radiation 13,14 .Yan et al, 2010, described the metabolism increase of skin fibroblasts and concluded that such behavior is due to resistance mechanisms of radiation cells 15 .Further studies, Yuasa et al, 2006, showed that the changes in protein expressions shall start with the interactions of radiation in the process of DNA replication, which can be occasional or permanent, and this gene reprogramming transmitted to new populations or new cell generations 16 . In additional studies, involving electromagnetic radiation such as cell phone signal or computer, Karinem et al, 2008, based on a female volunteer group, showed small changes in skin protein expressions although not conclusive 17 .…”
Section: Discussionmentioning
confidence: 99%
“…Falcão et al also found TGF and MMP9 metalloproteinase alterations in skin induced by UV radiation, which may be related to cancer induction 20 .Thus, protein transcription and proteomic irradiation effects causing physiological changes and the pathological establishment had already been observed. All proteomicreviewedstudies [10][11][12][13][14][15][16][17][18][19][20] were specific and targeted a physiological condition, and their findings cannot be generalized. However, those demonstrated the possibility of protein modulation induced by radiation in diverse human tissues.…”
Section: Discussionmentioning
confidence: 99%
“…/day) resulted in mutation in BRCA1 and TP53 genes [ [31] found that EMR caused different effects on c-Fos gene expression in the rat brain, Nylund & Leszezynski [32] showed that gene and protein expression were altered, in two variants of human endothelial cell line, in response to one hour mobile phone radiation exposure. Karien, et al [33] showed that the EMR alters protein expression in human endothelial cell line. On the other hand, Hung, et al [34] reported that EMR exposure did not produce significant changes in cell numbers, cell cycle distribution, or level of DNA damage or global gene expression.…”
Section: Discussionmentioning
confidence: 99%
“…Changes on gene/protein expression by RF exposure are also investigated. Leszczynskis group performed a pilot study on volunteers and showed that mobile phone radiation might alter protein expression in human skin cells [30]. Nittby et al [31] found that a large number of genes were altered at hippocampus and cortex using four exposed and four control animals.…”
Section: Motivationmentioning
confidence: 99%